Uma aplicação para o gerenciamento de competições esportivas universitárias - Ferreira, Hérick Pimentel (Brasil, 2024)
University sports are a form of athletic expression practiced within Higher Education Institutions, playing an important role in shaping students as citizens. This work presents the development of a web application for managing sports competitions, covering their modalities, teams, competitions, scores, and results. For this purpose, it was based on two iterative development models: the spiral and prototyping models, resulting in a final application that is satisfactory in terms of both usability and accessibility.